Violent and Sexual Offenders : Assessment, Treatment and Management - Ireland, Jane L.; Ireland, Carol A.; Birch, Philip; Taylor and Francis (Boca Raton, FL : Taylor and Francis, an imprint of Routledge, 2018)
Building on the success of the first edition and the growth of research in the field over the past decade, this book offers an authoritative overview of the assessment, treatment, and management of violent and sexual offenders. This new and expanded edition reflects the considerable developments in research and empirical data and captures the increasing breadth of risk assessment approaches, the wider range of empirically based therapies, and the more creative means of considering management. The second edition captures key developments in this area, with new chapters drawing on a range of pressing contemporary issues, such asfemale offenders, Internet offenders, terrorists, young people involved in harmful sexual behaviour, and protective factors for aggression. There is also extended coverage of the management of offenders within secure settings and in the community, referring to a wider variety of approaches and the incorporation of technology. This book will be of considerable interest to academics, practitioners, and students engaged with understanding and/or treating violence and aggression, sex crime, forensic psychology, and the assessment, treatment, and management of offenders.
Foreword (David P. Farrington) -- Section I: Risk assessment Current perspectives -- --1. Violence risk assessment (Robyn Mooney and Ivan Sebalo) -- --2. Thinking outside of the box: the assessment of sexual offending recidivism and specialist populations (Neil Gredecki and Kerensa Hocken) -- --3. Intimate partner violence risk assessment (P. Randall Kropp) -- --4. Assessment of internet-related sexual offenders (Derek Perkins) -- --5. Risk assessment and management of violent extremists and terrorists: Background, principles and practice (D. Elaine Pressman) -- --6. Assessing violence risk in youth (Andrew L. Gray, Catherine S. Shaffer, Jodi L. Viljoen, Nicole M. Muir and Tonia L. Nicholls) -- --7. Family Lovemap and protective factors: Sex, intimacy, and sexually abusive youth (L.C. Miccio-Fonseca) -- --8. Assessing women who sexually abuse children (Hilary J. Eldridge, Ian A. Elliott, Steven M. Gillespie, Alexandra Bailey and Anthony R. Beech) -- --9. Assessing violence and sexual risk among offenders with cognitive intellectual difficulties (Nicola Manning) -- --10. Protective factors for violence risk: Additional value to the risk focused approach (Michiel de Vries Robb) -- --11. Violence risk assessment in women: The value of the Female Additional Manual (Vivienne de Vogel, Miriam Wijkman and Michiel de Vries Robb) -- Section II: Clinical assessment Current perspectives -- --12. Individual assessments of aggression: Accounting for core factors (Jane L. Ireland) -- --13. Assessing the therapeutic needs of sexual offenders (Carisa Collins, Leigh Harkins and Laleh Dadgardoust) -- --14. Assessing the clinical needs for stalking and domestic violence (Werner Tschan) -- --15. Assessing the clinical needs for intellectually disabled sex offenders (Chanelle Salonia, Heather Hermans and David Hingsburger) -- --16. Assessing for psychopathy using the Psychopathy Checklist (Michael Lewis) -- --17. Using offence drivers to guide conceptualisation and treatment of trauma in male sex offenders (Ronald J. Ricci and Cheryl A. Clayton) -- --18. The background and clinical use of the Dynamic Appraisal of Situational Aggression Inpatient Version (DASA-IV): Application to a secure setting (Mark W. Thorpe, Panchu F. Xavier, Michael Daffern and Ashley L. Dunne) -- Section III: Treatment Current perspectives -- --19. Therapeutic treatment approaches for violence: Some essential components (Jane L. Ireland and Carol A. Ireland) -- --20. Treatment approaches for sexual violence (Carol A. Ireland and Rachel Worthington) -- --21. Adapting and evaluating treatment approaches for intellectually disabled sex offenders (John Rose) -- --22. Beyond traditional treatment approaches for intimate partner violence: Integrating a dyadic perspective (Lindsey M. Rodriguez, Nicholas A. Armenti and Julia C. Babcock) -- --23. Treatment of internet-related sexual offenders (Derek Perkins and Sarah Wefers) -- --24. Treatment approaches for stalking (Rosemary Purcell and Troy McEwan) -- --25. Treatment approaches for terrorists and extremists (Kurt Braddock) -- --26. Treatment approaches for women who sexually abuse children (Hilary J. Eldridge, Alexandra Bailey and Sheila Brotherston) -- Section IV: Management Current perspectives -- --27. Offender supervision and compliance: Managing violent and sexual offenders in the community (Chris Trotter) -- --28. Preventative detention and extended sentences: A regressive approach to managing violent and sexual offenders? (Andy Williams) -- --29. Managing violent and sexual offenders in contemporary technoculture (Mike Nellis and Nicol Shadbolt) -- --30. Sex Offender Registration and public protection: Rethinking the management of sex offenders in the community (Philip Birch and Emma Wintle) -- --31. The importance of throughcare and resettlement for working with violent and sexual offenders (Julie Trebilcock and Anne Worrall) -- --32. Desistance: Lessons learnt for managing violent and sexual offenders (Brian Stout) -- Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: Violent offenders; Sex offenders; Electronic books